Analysis of relative factors and prediction model for optimal ovarian response with gonadotropin-releasing hormone antagonist protocol - Jiang, Wenwen; Zheng, Beihong; Liao, Xiuhua; Chen, Xiaojing; Zhu, Suqin; Li, Rongshan; Zhang, Huale (Frontiers in Endocrinology, 2022)
Objective To explore the relative factors for best ovarian response in patients undergoing assisted reproductive technology with gonadotropin-releasing hormone (GnRH) antagonist protocol, and to establish a Nomogram prediction model of ovarian response. Methods A retrospective cohort analysis of the clinical data of 1944 patients who received assisted reproductive treatment in the Center for Reproductive Medicine of Fujian Maternity and Child Health Hospital from April 1, 2018 to June 30, 2020. According to the number of oocytes obtained, there were 659 cases in the low ovarian response group(no more than 5 oocytes were retrieved), 920 cases in the normal ovarian response group(the number of retrieved oocytes was more than 5 but less than 18), and 365 cases in the high ovarian response group( more than 18 oocytes were retrieved). Independent factors affecting ovarian responsiveness were screened by logistic regression, which were the model entry variables, and a nomogram prediction model was established based on the regression coefficients in the model. Results There were statistically significant differences in age, anti-Mullerian hormone (AMH) , antral follicle count (AFC), the diagnosis of endometriosis(EMT), Decreased ovarian reserve(DOR), polycystic ovary syndrome (PCOS), basal follicle-stimulating hormone (FSH) and basal luteinizing hormone (LH) among the three groups ( P <0.001). Multifactorial stepwise aggression analysis showed that female age[0.96(0.93-0.98), P=0.000], DOR [0.35(NA), P=0.000], EMT [0.76(NA), P=0.000], AFC [1.07(1.05-1.10), P=0.000], basal FSH[0.71(0.86-0.98), P=0.004], LH on trigger day [1.11(0.64-0.79), P=0.000], E2 on trigger day [1.00(1.00-1.00), P=0.000] were independent factors for the occurrence of different ovarian responses during ovarian hyperstimulation. The prediction model of ovarian responsiveness was constructed based on the above factors., and the model was verified with 589 patients' data from July 1, 2020 to December 31, 2020 in this center, and the predicted ovarian response (number of eggs obtained) of a total of 450 patients was consistent with the actual situation, with a coincidence degree of 76.4%. The consistency index of the model is 0.77.